The effects of whole-body vibration on EMG of leg muscles which are different fatigue resistant during static contractions - Simsek, D. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of the present study is to determine the effects of static whole body vibration (WBV) stimuli at low (2 mm) and high (4 mm) amplitudes and various frequencies (30-35- 40 Hz) on the neuromuscular responses of leg muscles which are different fatigue resistant. The fatigue protocol used for the determination of the fatigue index (FI).The study population was divided into two groups according to the values obtained by the FI (Group I: Less Fatigue Resistant (LFR), n=11; Group II: More Fatigue Resistance (MRF), n=11). Study results showed that LFR group that experienced a significantly higher percentage increase in the EMG activation values during higher frequencies (40 Hz) and amplitudes (4mm) (p<0,05). The highest level of muscular activation of MRF groups` was observed at 4 mm amplitude and 35 Hz frequency and thereafter tended to decrease (p<0,05).